Opening Skinner’s Box: an Introduction - Normand, Matthew P. (Behav Anal, 2014)
Behavior analysts have redefined the subject matter of psychology, redesigned the experiments used to study that subject matter, renamed almost every part of the world pertaining to that subject matter, and created specialized organizations and journals. It is not surprising, then, that only a happy few ever hear what behavior analysts say. One problem is that we need to publish outside of the box, so to speak. Preaching to the choir ensures that the products of our scientific behavior affect only a few people, limits the variety of reinforcers we are likely to encounter, and limits the likelihood that the products of our scientific behavior will reinforce the behavior of others. Publishing in a wider variety of outlets can lead to greater visibility for behavior-analytic research and practice, increase the impact of our published work, and build clout for scholars in colleges and universities.